Acehnese students’ perceptions toward their native English speaking teachers (NEST) - Nurul Inayah; Syamsul Bahri Ys; Nandira Syahnaz (Proceedings of AICS - Social Sciences, 2017)
This study intends to report the perceptions of 26 Syiah Kuala University students on the strengths and the weaknesses of their native-speaking English teachers (NESTs). Collected data include close-ended questionnaire with 18 (eighteen) questions and open-ended interview with 4 (four) questions.  Result of the study revealed that the students perceive the following as the NEST’s strength: creative in providing teaching materials, ideal model for pronunciation, and source of cultural information of the language. However some students were dissatisfied with the NEST’s performance in explaining grammars in the classroom. The result of the study indicates that even though NESTs are perceived as superior and a good model in teaching the target language, they also need to struggle with some obstacles in order to successfully teach the students.